Critical Success Factors for Stakeholder Engagement in Renewable Energy Projects of Malaysia - Zarith Sufia, Azlan; M., Waris; Puteri Fadzline, Muhamad Tamyez (Future Academy, 2019)
The development of renewable energy (RE) projects in Malaysia has gained attention in recent years and based on previous research, the implementation of effective stakeholder engagement (SE) brings positive outcomes to the RE projects. This paper carried out a systematic literature review covering all research published from 1999 to 2017, in the context of SE in the RE projects. Ten critical success factors were identified which were effective communication, continuous consultation, understanding the underlying intentions and behaviors, implementing strategy plans, building and sustaining good relationships, analyzing the changes, mitigating risks, compromising conflicts, understanding project success and good project governance. This study may aid both researchers and especially project managers in improving SE strategies and project outcomes in RE projects. However, an intervention framework is needed to indicate the effectiveness of SE in the whole project cycle and to validate if the level of critical success factors engaged is producing the desired results.